Dual closed-loop vector PI control and deadbeat current control of permanent magnet synchronous motor - Syed Abid Ali Shah Bukhari; Vikram Kumar; Muhammad Ahsan Niazi; Qazi Sajid (Sukkur IBA Journal of Emerging Technologies)
Permanent magnet synchronous motors (PMSMs) offer advantages such as high torque, power density, and energy efficiency, making them essential in power electronics, aerospace, and daily life. Designing PMSM control systems is complex yet crucial for optimizing performance. Field Oriented Control (FOC) is widely adopted due to its benefits including low torque ripple, high DC bus voltage utilization, and stable variable frequency speed regulation, aligning with diverse motor applications. However, achieving high-performance requires dynamic current loop control. Traditional Proportional-Integral (PI) control, though widely used, suffers from limited bandwidth and overshoot. Alternatively, deadbeat control, leveraging current prediction, offers superior dynamic response. In this study, deadbeat control demonstrates a significant improvement of approximately 20% in current loop response compared to PI control, as evaluated through simulations. Addressing challenges posed by varying motor parameters, this study incorporates Luenberger observer for parameter disturbance compensation, further enhancing control robustness by 15%. The effectiveness of the proposed method, emphasizing deadbeat control, is validated through Simulink simulations, promising a robust future for PMSM control.